Association of Geometric Characteristics of Knee Anatomy (Alpha Angle and Intercondylar Notch Type) With Noncontact ACL Injury. Issue 10 (August 2021) - Barnum, Michael S.; Boyd, Evan D.; Vacek, Pamela; Slauterbeck, James R.; Beynnon, Bruce D.
Background: The femoral intercondylar notch type and the alpha angle (the angle between the femoral notch roof and the long axis of the femur) are easily measured in clinical settings; however, their associations with anterior cruciate ligament (ACL) injury remain unclear. Hypothesis/Purpose: The purpose was to determine if the alpha angle and the femoral notch type are associated with noncontact ACL injury univariately and in combination with previously identified knee geometric risk factors. We hypothesized that the alpha angle and the femoral notch type are associated with noncontact ACL injury and that the association differs between men and women. Study Design: Case control study; Level of evidence, 3. Methods: The alpha angle and the femoral notch type were measured via 3T magnetic resonance imaging (MRI) acquired from 61 women and 25 men with a first-time noncontact ACL injury. Each injured patient was matched with a control participant based on age, sex, and participation on the same sports team. A conditional logistic regression was used to assess univariate associations with ACL injury as well as multivariate associations using MRI-based risk factors of knee geometry identified in previous analyses: femoral intercondylar notch width at the anterior outlet, femoral intercondylar notch anteromedial ridge thickness, volume of the ACL, tibial plateau lateral compartment subchondral bone slope, lateral compartment middle articular cartilage slope, lateral compartment meniscus-cartilage height, lateral compartment meniscus-bone angle, and medial tibial spine volume. Results: For female athletes, the alpha angle (odds ratio, [OR], 1.82 per 1-degree increase; P = .001), the tibial lateral compartment articular cartilage slope (OR, 1.25 per 1-degree increase in the posterior-inferior directed slope; P = .022), and the femoral notch anteromedial ridge thickness (OR, 3.36 per 1-mm increase; P = .027) were independently associated with ACL disruption. For men, no other variables entered the models after the alpha angle was inputted as the first step (OR, 2.19 per 1-degree increase; P = .010). Conclusion: For women, ACL injury was most strongly associated with increased alpha angle, increased tibial plateau slope, and increased femoral notch ridge thickness. For men, increased alpha angle was the most significant factor associated with ACL injury. The mechanism of injury might be associated with a combination of impingement of the ACL against the bone and increased ligament loading.